2017
DOI: 10.1111/jbi.12995
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of deermice (Rodentia: genus Peromyscus) at their north‐western range limit: genetic consequences of refugial and island isolation

Abstract: Aim We surveyed the genetic variability of deermice (genus Peromyscus) at the north‐western edge of their range to test for occupancy in multiple, hypothesized ice‐free regions during the late Pleistocene and explore post‐glacial dynamics. Location North‐western North America. Methods We used sequences from four independent nuclear and mitochondrial loci from 341 specimens of Peromyscus maniculatus, Peromyscus keeni and Peromyscus sp. (Yukon) to assess species limits, population structure, and demographical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…We have shown that contact and mixing of lineages colonizing from the Carpathian and Eastern LGM refugia has contributed to the high genetic diversity observed at the regional level in populations of the bank vole in Fennoscandia. This supports the role of admixture between genomes originating from different refugia as a process reducing the influence of repeated founder events otherwise expected to result in low genetic diversity outside the refugial areas (Gömöry, Paule, Krajmerová, Romšáková, & Longauer, 2012; Havrdová et al., 2015; Neophytou & Michiels, 2013; Pedreschi et al., 2019; Rowe, Heske, Brown, & Paige, 2004; Sawyer, Flamme, Jung, MacDonald, & Cook, 2017; Tollefsrud et al., 2008; Widmer & Lexer, 2001). However, our results show that it is not only the admixture of long‐isolated populations originating from different refugia that can enhance genetic diversity in a colonized area, but increased diversity can also represent admixture from multiple colonizations originating from the same refugium.…”
Section: Discussionsupporting
confidence: 52%
“…We have shown that contact and mixing of lineages colonizing from the Carpathian and Eastern LGM refugia has contributed to the high genetic diversity observed at the regional level in populations of the bank vole in Fennoscandia. This supports the role of admixture between genomes originating from different refugia as a process reducing the influence of repeated founder events otherwise expected to result in low genetic diversity outside the refugial areas (Gömöry, Paule, Krajmerová, Romšáková, & Longauer, 2012; Havrdová et al., 2015; Neophytou & Michiels, 2013; Pedreschi et al., 2019; Rowe, Heske, Brown, & Paige, 2004; Sawyer, Flamme, Jung, MacDonald, & Cook, 2017; Tollefsrud et al., 2008; Widmer & Lexer, 2001). However, our results show that it is not only the admixture of long‐isolated populations originating from different refugia that can enhance genetic diversity in a colonized area, but increased diversity can also represent admixture from multiple colonizations originating from the same refugium.…”
Section: Discussionsupporting
confidence: 52%
“…The range of the Island clade of M. longicaudus is limited to the AA and nearby mainland, a distribution consistent with their paleoendemism in the region (Figure ). The distributions in both P. keeni and the Island clade of S. monticola (south to Washington) extend beyond SE Alaska, but divergence dates, net genetic distance, genetic diversity, and expansion statistics, as well as models of refugial migration for P. keeni (Sawyer, Flamme, Jung, MacDonald, & Cook, ), suggest these species persisted along the coast during the LGM. The finding of an island paleoendemic clade for all three species is consistent with the phylogeographic pattern uncovered for ermine ( Mustela erminea ) in the region (Colella et al, ), but differs somewhat from two other carnivores, Pacific Coast marten ( Martes caurina ) and black bear ( Ursus americanus ), where the distribution of the island lineages now extend far beyond the boundaries SE AK (Dawson et al, ; Fleming & Cook, ; Peacock et al, ; Small, Stone, & Cook, ).…”
Section: Discussionmentioning
confidence: 99%
“…. The distributions in both P. keeni and the Island clade of S. monticola (south to Washington) extend beyond SE Alaska, but divergence dates, net genetic distance, genetic diversity, and expansion statistics, as well as models of refugial migration for P. keeni(Sawyer, Flamme, Jung, MacDonald, & Cook, 2017), suggest these species persisted along the coast during the LGM. The finding of an island paleoendemic clade for all three species is consistent with the phylogeographic pattern uncovered for ermine (Mustela erminea) in the region(Colella et al, 2018), but differs somewhat from two other carnivores, PacificCoast marten (Martes caurina) and black bear (Ursus americanus),…”
mentioning
confidence: 93%
“…are cryptic, with up to 3 species occurring in some regions (Sawyer et al 2017). However, based on detailed genetic analyses by Sawyer et al (2017), deer mice in our study areas were likely all P. maniculatus. Captured small mammals were sexed by external examination, and mass was obtained with a digital scale (±0.1 g).…”
Section: Methodsmentioning
confidence: 82%
“…In the Yukon, species of deer mice ( Peromyscus spp.) are cryptic, with up to 3 species occurring in some regions (Sawyer et al 2017). However, based on detailed genetic analyses by Sawyer et al (2017), deer mice in our study areas were likely all P .…”
Section: Methodsmentioning
confidence: 99%